(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Technology advances by the day and computers can be considered as valuable to almost every learned person. One of the most uses of computers nowadays is for internet surfing and social networking. Computers in this context are not restricted to desktop or laptop computers only. Internet surfing and social networking has made interactions between people and computers very easy, where people can communicate using their languages thus making processing of these languages a useful task for the computers to interpret. The correct processing of these languages on the computer relies on the correct identification of parts of speech (POS) in sentences which has been an active area of research for a long time. This paper presents a review parts of speech tagging, comparison of different tagging techniques, their characteristics, difficulties, limitation, and Multilingual Parts of Speech (POS) tagging approaches.